Induced Apical Closure of Nonvital Immature Root Apices with Mta - Singh, Shikha; Singh, Sweta; Munaga, Swapna; Maurya, Gautam Singh (Journal of Orofacial Research, 2014)
Endodontics is a specialty which is very receptive to new ideas and concepts. Management of open apex is a challenge to the endodontist. The treatment of choice for necrotic teeth is apexification,  which is induction of apical closure to produce more favorable conditions for conventional root canal filling. The most commonlyadvocated medicament is calcium hydroxide, althoughrecently considerable interest has been expressed in the use of mineral trioxide aggregate. Introduction of techniques for one-visit apexification provide an alternative treatment option in these cases. Research, published studies, and clinical results support this material, and have served to increase the expectation that nonsurgical treatment success is both possible and attainable. This paper highlights a case reports for apexification using  mineral trioxide aggregate.